IMPLEMENTATION OF RELIGIOUS MODERATION AS AN EFFORT TO DERADICALISM AGAINST CORRECTIONAL INMATES (WBP) IN CORRECTIONAL INSTITUTIONS (LAPAS) CLASS IIA PALOPO - Rahmawati; Abdain; Takdir (UIN Palopo, 2026)
This study aims to analyze the deradicalism system program implemented in Class IIA Palopo Penitentiary; analyze the religious moderation mentoring system program; and analyze the efforts made to minimize radicalism behavior among inmates in Class IIA Palopo Penitentiary. Data collection techniques were carried out through observation, counseling, interviews and documentation. The research informants used were the head of the correctional institution, officers, and inmates. While data analysis used data reduction techniques, data presentation and conclusion drawing. The results of the study showed that; First, the deradicalism system program implemented in the correctional institution is to hold spiritual guidance which aims to provide spiritual guidance so that inmates can behave moderately. Second, the religious moderation mentoring system program is carried out using the CBR approach where the CBR system consists of several stages in the form of a non-linear rectangle and repeats phases that are in harmony and adaptive to the existing context so that the learning process occurs continuously. Third, efforts made to minimize radicalism among inmates in correctional institutions are increasing the role of BNPT in collaboration with various parties such as the police, Correctional Institutions, Ministry of Religion, Coordinating Ministry for People's Welfare, mass organizations, and so on such as; providing special guidance to prisoners and increasing prisoner nationalism. The implications of the research are strengthening correctional institutional reform and instilling the values of nationalism and religious personality as a necessity in order to combat terrorism, while protecting community groups.